CLINICAL EFFECTIVENESS OF LOCAL HARMFUL PRESSURE METHOD IN THE COMPLEX TREATMENT OF PURULENT WOUNDS: // Collection of abstracts of the scientific and practical conference «Current Problems of Surgical Soft Tissue Infections» (2024), Tashkent, October 28 - Kurbanov, E.Y.; Kasimov, U.K. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
In recent years, the problem of treating acute and chronic purulent processes (PP) has become increasingly urgent. Despite developing new antibacterial and immunological preparations, purulent-septic diseases have not decreased. In the structure of population mortality from infectious pathology, purulent-septic diseases occupy the first place in all developed countries of the world. Currently, patients with purulent pathology make up to 30% of all surgical patients. Strengthening of virulence of microorganisms, growth of their resistance to antibiotics and antiseptics, a decrease of the immunological status of macroorganisms, accession of fungal lesions, frequent development of purulent-septic diseases on the background of diabetes mellitus requires the introduction of new pathogenetically grounded and sparing methods of treatment of purulent-septic diseases becomes an integral task of purulent surgery—the purpose of the study. The study aimed to determine the effectiveness of the local negative pressure (LNP) method in treating purulent wounds.